Corrosion Control Management of Pipelines of Oil and Gas Industries - Atienza, Marisol; Aloria, Michael (International Journal of Sustainability and Advanced Integrated Research, 2026)
Corrosion in oil and gas pipelines poses significant risks to operational reliability, economic performance, environmental safety, and public welfare, particularly in coastal and high-humidity regions. This study aimed to assess corrosion risks in oil and gas pipeline systems in Batangas Province, Philippines, and to develop a structured, risk-based Corrosion Control Management System (CCMS) to support effective decision-making. Anchored on Failure Mode and Effects Analysis (FMEA), the study employed a mixed-method research design integrating site observations, structured interviews, document review, and quantitative risk analysis. Respondents included engineers, maintenance personnel, corrosion specialists, and technical staff from six oil and gas companies operating pipeline systems in Batangas. Environmental and operational factors contributing to corrosion were identified, including coastal exposure, soil composition, humid tropical climate, pipeline pressure, temperature, and transported fluid composition. FMEA results identified ten major corrosion-related failure modes, with microbiologically influenced corrosion, internal corrosion, soil-side corrosion, and delayed corrosion detection ranked as the most important based on Risk Priority Numbers. Variability analysis further indicated that certain failure modes require site-specific verification due to differences in operating conditions and inspection practices. Based on these findings, a CCMS was developed by integrating risk prioritization, variability assessment, and corrosion control selection aligned with recognized international standards. Evaluation of the proposed CCMS indicates its potential to reduce corrosion-related maintenance costs, minimize unplanned downtime, and lower the likelihood of environmental incidents through preventive, risk-based interventions. The study concludes that systematic integration of FMEA into corrosion management enhances pipeline integrity, operational efficiency, and environmental protection. The research supports Sustainable Development Goals related to Industry, Innovation and Infrastructure (SDG 9), Responsible Consumption and Production (SDG 12), Climate Action (SDG 13), and Decent Work and Economic Growth (SDG 8) by promoting safe, efficient, and sustainable pipeline operations. The sustainability impact of the study lies in strengthening institutional risk governance, reducing environmental risks associated with corrosion-related failures, and supporting long-term infrastructure resilience in the energy sector.
Keywords: Corrosion control management system; Failure Mode and Effects Analysis; microbiologically; corrosion; oil and gas pipelines; pipeline corrosion; risk assessment; sustainability; tropical coastal environment